The financial accelerator and market-based debt instruments: A role for maturities? - Michael Kühl (Deutsche Bundesbank, 2014)
This paper shows how the average maturity of corporate bonds can affect the transmission of shocks if financial frictions prevail. We modify a standard financial accelerator model à la Bernanke, Gertler, and Gilchrist (1999) and allow for market-based debt which has a market-determined price. Our results show that the average maturity of bonds is essential for the transmission of shocks. The dynamics are largely identical to the standard BGG model for shorter maturities, while the model behaves differently for longer maturities. In this case a prolongation channel becomes apparent which attenuates the original amplification mechanism.
Keywords: E3; E44; G3; 330; DSGE Model; Financial Frictions; Maturites; Financial Accelerator; Capital Market